QR Code, Face Recognition, and Google Location as Alternative Solution for Employee’s Attendance in Small Companies - Oscar Wongso (Maranatha University Press, 2016)
RFID and biometric time attendance have been used to taking employee’s attendances in attendances. But they have disadvantage which is cost a lot in terms of prices when need to be used in several places at the same time. An alternative solution was given by using android application which utilizing QR-Code, Face Recognition, and Google Map Location technologies implemented in smartphone to taking employee’s attendances. A test for this system was conduct on one of private colouring studios in Bandung, and from the results shown that using this android application help the employees to take attendances. This paper explains the architecture, design, research findings, and future improvements of attendance system.